2022
DOI: 10.1111/jpm.12878
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of extrinsic and intrinsic factors on psychiatric nurses’ spiritual care attitudes

Abstract: Accessible Summary What is known on the subject? Because the definition of spirituality is complex and has cultural and individual dimensions, it is important to be receptive to individual differences in the perception of spirituality during clinical practice of mental health nurses. Although enhancing spiritual care is beneficial to patients diagnosed with mental illnesses, the extrinsic (e.g., education) and intrinsic factors that would affect nurses' attitudes towards spiritual care have not been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Of course, the main studies have previously looked at clinic patients or representatives of various professions, without considering the gender issue (Chou et al, 2017;Cormack et al, 2000;Moore & George, 2011). For example, some internal social intelligence factors associated with personality -Extraversion, Openness/Intelligence, Consciousness, and Pleasantness -are associated with a higher awareness of the need for spiritual care among mental health nurses (Han et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of course, the main studies have previously looked at clinic patients or representatives of various professions, without considering the gender issue (Chou et al, 2017;Cormack et al, 2000;Moore & George, 2011). For example, some internal social intelligence factors associated with personality -Extraversion, Openness/Intelligence, Consciousness, and Pleasantness -are associated with a higher awareness of the need for spiritual care among mental health nurses (Han et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding demographic variables, except prior hospitalization experience, there has been no significant correlation observed between competence to provide spiritual care and other factors including age, sex, marital status, and work experience [11]. In addition, a recent cross-sectional study that explored the factors influencing the attitudes of mental health nurses toward spiritual care highlighted both extrinsic factors, such as postgraduate education, working experience, participation in palliative care education programs, and spiritual care experience, as well as intrinsic factors like personality traits (e.g., Extraversion, Openness/Intellect, Conscientiousness, and Agreeableness), which were associated with greater awareness and inclination toward providing spiritual care [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies explored the attitudes of psychiatric nurses towards mental disorders and found that the attitudes of psychiatric nurses to patients with mental disorders were basically as negative as those of the general population, but were significantly more negative and stereotypical than those of other mental health professionals, such as psychiatrists, psychologists and social workers ( 14 16 ). In addition, a cross-sectional study noted that psychiatric nurses’ attitudes towards mental disorders were significantly associated with their clinical experience in mental health services, i.e., the more clinical experience they had, the more positive their attitudes towards mental disorders were ( 17 ). The results of these studies suggested that attitudes towards mental disorders might be related to the contents and forms of psychiatric education.…”
Section: Introductionmentioning
confidence: 99%